Favourite fast food among UiTM Pasir Gudang students - Anak Intai, Nigel Nyelang; Zulkarnain, Muhammad Amin; Mohd Ridzwan, zzah Farzana; Kelana, Nur Illy Adawiyah; Mazlan, Fatin Nursyifa; Alimon, Nur Idayu (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Fast food is quick to prepare, simple to access, reasonably affordable, and tastes well. They frequently come in huge servings and are high in salt, sugar, and energy but poor in fibre and minerals. Numerous studies have documented a number of adverse consequences linked to fast food eating, from childhood weight gain to an increased risk of diabetes. A diet that is high in calories, saturated fat, as well as body fatness, and many more has been related to increased fast food intake, which can have an adverse effect on one’s health. The combination of these nutritional elements and a sedentary lifestyle may cause health issues. The objectives of this study is to determine and find the factor of choosing fast food among UiTM students. Then, the mean and median of the chosen fast food are calculated and the consumer’s weekly/monthly spend is evaluated. The advantage of choosing fast food is people can reduce their time to prepare a food but too much of fast food consumption can lead to a rapid spike in blood sugar. In conclusion, it can be concluded that the modern style of life in our societies gave rise to fast food. Unfortunately, it has negative impacts on the body and health of people